Energy Management: A polish case study - Majchrowicz, J. (2011)
Grupa LOTOS, a vertically integrated oil company working in the field of crude oil production, refining, and oil products distribution, employs an online model, Visual MESA, to monitor and optimize the energy system. The energy system is based around several steam pressure levels, with a set of fired boilers producing high pressure steam, a set of steam turbo generators producing electricity, and a set of process heaters which can run with fuel gas and fuel oil. The steps of the system include data collection and control system review, software installation, model building and optimization configuration, midpoint review and users training, and burn in period. An important monitoring aspect of the system include the continuous auditing of the energy system so the data can be relied on for evaluating the value of energy production and usage, and waste can be eliminated. Imbalances are flagged graphically by using balloons of different colors and sizes.